(untitled) (Gragoatá, 2021)
Data from plurilingual Belize shows that not everyone recognizes stability as an essential feature of a spoken language. Belizeans consider the use of Kriol as a symbol of belonging but foreground its readiness for variation across communities in space and time. Their use of liquid languages is a different form of cultural construction than the one our textbooks show. It questions a good part of linguistics and reveals its possibly Eurocentric point of view.